Pandangan John Calvin Mengenai Spiritualitas Anak dalam Konteks Pendidikan Kristen - Paulus Dimas Prabowo; Ninik Triutami; Norce Lenora Saleky; Marlina Nasrani Juliana; Urbanu Dacosta (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
In this modern era, children's spirituality is often neglected in the education and childcare system. In an increasingly secular society, religious and spiritual values ​​are often considered irrelevant to the challenges of the times. Calvin, through his various writings, emphasized the importance of understanding children as God's precious creation, as well as individuals who need guidance in the faith. This article aims to prove that Calvin had views on children's spirituality that could be linked to Christian education. Through the literature study method, there are several important findings. First, Calvin had a clear view of the spiritual condition of children based on the doctrine of original sin which could only be resolved through Christ. Second, Calvin views children's spirituality as important, as a personal relationship with God and learning Biblical teachings that shape daily thought patterns and behavior. Third, Calvin's thoughts contributed to Christian educational institutions thinking about a curriculum that includes the practice of reading the Bible, introducing doctrine and disciplining children.